The Effect of Compensation, Leadership Style, and Work Environment on Employee Performance at Pt. XYZ - Sri Diana Salma Nurul Aini; Sudarijati; Rachmat Gunawan (Asian Journal of Applied Business and Management, 2023)
Employee performance is one of the most influential factors in the company's work system. Compensation, leadership style, and a good work environment can motivate employees to work harder and employee performance productivity will increase. So the company must be able to pay attention to compensation, leadership style and work environment conditions. This study aims to determine the effect of compensation, leadership style, and work environment, on the performance of employees of PT XYZ. This research data consists of primary and secondary data. Primary data obtained from the results of questionnaires to 41 employees. The results of this study based on the results of validity and reliability tests show that all indicators are declared valid and reliable. Simultaneously compensation, leadership style, work environment, affect the performance of PT XYZ employees. While partially all independent variables affect employee performance